2021
DOI: 10.1093/dote/doab052.544
|View full text |Cite
|
Sign up to set email alerts
|

544 Management of Acute Anastomotic Complications After Ivor-Lewis Esophagectomy

Abstract: Anastomotic leak (AL) and conduit necrosis (CN) are among the most serious surgical complications after esophageal resection. Endoscopic, radiological and surgical methods are used in their treatment. The aim of this paper is to evaluate the results of the treatment of acute anastomotic complications after Ivor-Lewis esophagectomy in a single high-volume center. Methods We performed a retrospective audit of a consecutive cohort of 815 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Although the groups of patients included in the studies vary, the rate of successful fistula closure by stenting varies between 63.5 and 100% [16,[22][23][24]. Segura et al in a 2022 study reported fistula healing using a single stent with the covered double-layer metal stent (Niti S™ DOUBLE™ Esophageal Metal Stent Model) in a percentage of 75% and 100% in terms of using the method [25], and Haruštiak et al revealed an efficiency of 84% in closing the fistula by stenting in an average time of 55.7 ± 27.11 days/patient (mean of 39 ± 24.30 days/stent) [26].…”
Section: The Efficiency Of the Methods In The Treatment Of Fistulamentioning
confidence: 99%
See 2 more Smart Citations
“…Although the groups of patients included in the studies vary, the rate of successful fistula closure by stenting varies between 63.5 and 100% [16,[22][23][24]. Segura et al in a 2022 study reported fistula healing using a single stent with the covered double-layer metal stent (Niti S™ DOUBLE™ Esophageal Metal Stent Model) in a percentage of 75% and 100% in terms of using the method [25], and Haruštiak et al revealed an efficiency of 84% in closing the fistula by stenting in an average time of 55.7 ± 27.11 days/patient (mean of 39 ± 24.30 days/stent) [26].…”
Section: The Efficiency Of the Methods In The Treatment Of Fistulamentioning
confidence: 99%
“…In order to reduce the consequences of a persistent post-stenting fistula, it is necessary that it be recognized and managed properly. The reported incidence of fistula persistence varies but may be seen in approximately 10-38% of patients [24,26,[34][35][36]. Stephens et al [19] proposed in 2014 a classification of persistent post-stent fistula into five types based on radiographic evaluation with water-soluble contrast: Type 1-proximal; Type 2-retrograde distal; Type 3-through holes in the film covering the stent; Type 4-between stents; and Type 5-migrated stent.…”
Section: The Persistence Of the Leak After Stent Placementmentioning
confidence: 99%
See 1 more Smart Citation